Chicken soup for the soul like mother like daughter : stories about the special bond between mother and daughters - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Chicken Soup for the Soul Pub., 2012)
A collection of 101 true personal stories by mothers and daughters of all ages about the magical relationship between mothers and daughters, with stories ranging from funny to inspirational to heartwarming.